Influence of the quality of remote education on the satisfaction of Colombian university students - Paredes-Daza, Javier David; Niño-Vega, Jorge Armando; Fernández-Morales, Flavio Humberto (Gaceta Médica de Caracas, 2025)
Background: In the global context of increasing reliance on remote education, driven by diverse circumstances, examining how its quality influences student experience and satisfaction is imperative. Such analysis is crucial for identifying areas of improvement and ensuring that remote education aligns with the standards required for effective learning. Accordingly, this study aims to evaluate the impact of the quality of remote education on student satisfaction at a higher education institution in Colombia. Methods: This research employs a quantitative approach with a non-experimental design, utilizing convenience sampling to survey 520 undergraduate students from a public university. Data was analyzed using exploratory factor analysis and Spearman correlation.